(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Toxoplasmosis is one of the risky infection my lead to cardiovascular diseases. One hundred therein patients samples were collected with Heart Diseases and there were infected with Toxoplasmosis, in Baghdad educational Hospital from period 1st January 2019 to 1st September 2019. The results show that prevalence of Toxoplasma gondii among Hypertensive disease and Myocardiopathy with Heart Diseases. The genotype of MYLK3 exon to Human cardiac gene by gel electrophoresis, Lane M markers correspond to 500 bp ladder lane 2 of gene band with 600bp. Mutation occurrence in exon 8 the gene sequence CCCAGCCGG were change to CCCATCCGG, and in exon 9 the change occurrence in sequence CTCAAGCCGGAG to CTCAAGGTACAA